Eslicarbazepine Acetate Modulates EEG Activity and Connectivity in Focal Epilepsy - Pellegrino, Giovanni; Mecarelli, Oriano; Pulitano, Patrizia; Tombini, Mario; Ricci, Lorenzo; Lanzone, Jacopo; Brienza, Marianna; Davassi, Chiara; Di Lazzaro, Vincenzo; Assenza, Giovanni (Frontiers in Neurology, 2018)
Introduction Eslicarbazepine acetate (ESL) is an antiepileptic drug approved as monotherapy or add-on for the treatment of epilepsy with seizures of focal onset. ESL owns a good profile in terms of efficacy and tolerability, but its effects on EEG activity and connectivity are unknown. The purpose of this study was to investigate EEG activity and connectivity changes after ESL treatment in persons with focal epilepsy (PFE). Material and Methods We performed a multicentre, longitudinal, retrospective, quantitative EEG study on a population of 22 PFE and a control group of 40 controls. We investigated the ESL-related changes of EEG power spectral activity and connectivity (phase locking value (PLV), amplitude envelope correlation (AEC) and amplitude envelope correlation of orthogonalized signals (Ortho-AEC)) for standard frequency bands (delta to gamma). Seizure frequency was evaluated to assess ESL efficacy in our cohort. Results ESL significantly enhanced both global power spectral density and connectivity for all frequency bands, similarly for all connectivity measures. When compared to the control group, Post-ESL power was significantly higher in theta and gamma band. Pre-ESL connectivity values were significantly lower than control for all frequency bands. Post-ESL connectivity increased and the gap between the two groups was no longer significant. ESL induced a 52.7±41.1% reduction of seizure frequency, with 59% of clinical responders (reduction of seizures ≥50%). Discussion ESL therapy induces significant enhancement of brain activity and connectivity. Post-ESL connectivity profile of epilepsy patients was similar to the one of healthy controls.